SEM PLS ANALYSIS EFFECT OF MORALE AND COMPENSATION ON ACADEMIC PERFORMANCE (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
The purpose of the study was to examine the effect of morale and compensation on academy performance with organizational culture as a mediationvariable. The population and sample of this study throughout the academy at Siteba Health Polytechnic with sampling techniques using a total sampling technique of 46 people. The results of this study show that (1). Variable morale and compensation have a direct and significant effect on organizational culture. (2) Morale, compensation and organizational culture have a positive and significant effect on academic performance. (3) The mediation effect of organizational variables was found to affect morale and compensation for academic performance